The impact of pulmonary rehabilitation on the parameters of spirometric examination and six-minute walk test of patients with respiratory dysfunctions (chronic obstructive pulmonary disease or asthma) aged 50-70 years hospitalized at the Pulmonary Rehabilitation Ward in the Pulmonary-Cardiological Specialistic Hospital in Torzym - Anna Złotnik; Agata Bloch; Anna Kałużna; Magdalena Hagner-Derengowska; Krystian Kałużny; Walery Zukow (Kazimierz Wielki University, 2018)
Spiroergometric exercise test and a six-minute march test are methods for assessing the exercise capacity. They are used to determine diagnostic and prognostic information, treatment and its effectiveness. The article presents the main parameters evaluated during the tests. The examined disease entities were presented and described, and conclusions from the research were drawn.